Integrating Hydrogeological and Microbiological Data and Modelling to Characterize the Hydraulic Features and Behaviour of Coastal Carbonate Aquifers: A Case in Western Cuba - Rebeca Hernàndez-Diaz (Water, 2019)
Carbonate aquifers are the primary source of freshwater in Cuba. Unfortunately, coastal groundwater is often contaminated by seawater intrusion. The main aim of the present study was to test the efficacy of an experimental modelling approach, ranging from hydrogeology/geomorphology to microbiology, to better characterise both the hydraulic features and behaviour of a coastal carbonate aquifer and acquire useful information to prevent groundwater salinization. The interdisciplinary approach was an effective tool in order to understand (i) the hydraulic role played by some fault zones; (ii) the influence of discontinuous heterogeneities on groundwater flow and saltwater wedge shape; (iii) mixing processes between different water bodies (groundwater, surface water, seawater); (iv) the role of karst conduits in influencing the step-like halocline within the mixing zone between fresh groundwater and seawater.